PPP at Low Latitudes With Ionospheric Model Exclusively Based on Single Frequency GNSS Measurements - Christovam, Ana L. [UNESP]; Prol, Fabricio S.; Jerez, Gabriel O. [UNESP]; Hernández-Pajares, Manuel; Camargo, Paulo O. [UNESP] (American Geophysical Union (AGU), 2023)
Single frequency users of the Global Navigation Satellite System (GNSS) should correct the ionospheric delay to obtain positioning solutions. A valuable source of ionospheric delay corrections is the global ionospheric models (GIMs) of Vertical Total Electron Content. The accuracy of GIMs is therefore important to improve the positioning accuracy. One of the main issues that affects the GIM performance, especially at low latitude regions, is the high sensitivity of the global positioning system (GPS) L2 frequency to ionospheric scintillation. As an attempt to overcome this issue, in this work, we study the capabilities of using only GPS L1 frequency to compute ionospheric corrections in form of regional ionospheric maps. The performance of the new ionospheric model is evaluated by means of single frequency precise point positioning, comparing the positioning results against the correction using dual-frequency GPS signals, as well as compared to the corrections provided by GIMs produced by the international GNSS service. As a result, the positioning performance using single frequency model presented similar accuracy to the dual frequency models and, at the same time, provided less observations affected by ionospheric scintillations. These results demonstrate the feasibility of using single frequency GNSS data to develop ionospheric models and to improve the positioning over low latitudes.
Keywords: GIM; GPS; ionospheric delay; kinematic PPP